The effect of five polishing materials on the surface roughness of acrylic and composite denture resins - (:unkn) unknown (Trans Tech Publications Ltd, 2012)
Rough surfaces of denture prosthesis promote adhesion of microorganisms and plaque formation. In dentistry ferric oxide, tin oxide, chrome oxide and pumice are the most commonly used materials for polishing of resins and other materials. Clinoptilolite that is in zeolitic structure resembles to pumice due to alumina silicate formations in its constitution. Surface roughness was evaluated by means of a surface roughness analyzing instrument, Perthometer There were 10 specimens for each acrylic resin and bis-acryl composite resin material and polishing method combination. Conventional lathe polishing with polishing paste served as surface roughness was determined with a profilometer and SEM microscope. ANOVA was applied to the all measurements and was statistically significant (p<0.001). The p-values were calculated using paired t-tests. The materials in order that are most successful at polishing PMMA surface are; clinoptilolite Ra 0,5 > Fe2O3 Ra 0,6 > Cr2O3 Ra 0,8> pumice Ra 1,2 > SnO2 Ra 1,6. the surface roughness values for Bisacryl Composite are as follows: clinoptilolite Ra 0,6 > Fe2O3 0,8 Ra > Cr 2O3 Ra 0,9 > pumice Ra 1,4 > SnO2 Ra 1,9. The most successful material for PMMA and Composite resin were clinoptilolite followed by; clinoptilolite, Fe2O3, Cr2O 3, pumice, and SnO2 in order. The same results were confirmed with the scanning electron microscopic images. Within the light of the present study Clinoptilolite can be an alternative to pumice for polishing of PMMA. © (2012) Trans Tech Publications.
Keywords: Chrome oxide; Clinoptilolite; Dental polish; Ferric oxide; Pumice; Surface roughness; Tin oxide